Comparison of analysis methods for determination of dynamic tissue conductivity during microseconds-long pulsed electric fields. (February 2022) - Beitel-White, Natalie; Lorenzo, Melvin F.; Zhao, Yajun; Aycock, Kenneth N.; Manuchehrabadi, Navid M.; Brock, Rebecca M.; Coutermarsh-Ott, Sheryl; Imran, Khan Mohammad; Allen, Irving C.; Davalos, Rafael V.
Highlights: Prostate and prostate tumor showed dynamic conductivity during 5 and 10 microsecond H-FIRE. Pancreas, liver, and brain porcine tissue showed little electric field dependence during H-FIRE. Most tissues behaved approximately as a resistive load in response to the H-FIRE pulses. Abstract: Objective: High-frequency irreversible electroporation (H-FIRE) is an emerging therapy which uses bursts of high-voltage, bipolar pulses to ablate tissue. This paper aims to quantify electric-field-dependent material properties of select tissues for computational models. The results show that tissues treated with 5 and 10 μs H-FIRE can be approximated as purely resistive, simplifying analysis and numerical modeling. Methods: Parallel-plate electrodes were used to apply H-FIRE waveforms (5-5-5 and 10-1-10) to samples of porcine pancreas, liver, prostate, brain, and patient-derived prostate tumor. Resistance of each sample during pulsing was calculated from captured current waveforms using two methods for comparison: one assuming a purely resistive response from tissue and the other assuming dispersion. Results: Conductivity versus electric field (EF) behavior is reported for all five tissue types. There was little dependence of conductivity on EF magnitude for most tissues except for prostate and prostate tumor tissue. Additionally, the study found that differences between the two resistance analysis methods were less than 10% except for prostate ( < 30%) and liver and pancreas at lower EF magnitudes. Conclusion: Prostate and prostate tumor tissues are expected to undergo more EF redistribution during H-FIRE as compared with the other tissues. Also, in most cases under study, the results suggest that frequency effects are minimal using these particular waveforms. Significance: Currently, high-frequency effects on tissue properties that occur during microseconds-long bipolar pulses are not yet clear and quantified. This work reports these properties while also assessing whether approximation of the tissue as resistive is appropriate.